Consumption and Sustainable Management: Exploring Visitor Expenditures and Influencing Factors in Urban Parks - Peng Zhan; Qinghai Guo; Zhong Zheng; Zheng Chen (Ecosystem Health and Sustainability, 2025)
Urban parks serve not only as recreational spaces but also as venues for visitor expenditures, which can generate revenue to alleviate financial pressures on park management. However, current understanding of spending patterns in urban parks remains limited. This study investigates visitor expenditures on food, drinks, shopping, transportation, and cultural/recreational activities in Hangzhou’s urban parks, analyzing the underlying mechanisms. The results reveal an average expenditure of 140.61 CNY per visitor, with food (49.32 CNY), transportation (32.29 CNY), and drinks (19.27 CNY) accounting for the largest shares. Drinks were the most commonly reported expenditure item, with 65.84% of visitors making such purchases. Monthly income emerged as the most important predictor of spending, with higher-income visitors demonstrating greater expenditures. Three pathways through which park environments affect expenditures were identified and validated: (a) direct effects (e.g., the density of internal businesses), (b) attraction of high-spending visitor segments, and (c) indirect effects mediated by park usage behaviors and psychological factors. These findings offer new insights into the characteristics and drivers of visitor consumption in urban parks. They provide practical implications for urban planners and park managers seeking to develop commercial strategies that align with visitor expenditures patterns. By fostering a nature–economy interaction, such strategies can support the sustainable management of urban parks.